Primary central nervous system plasmablastic lymphoma in an HIV-positive patient. Issue 3 (14th March 2019) - Rhoades, Ruben; Gong, Jerald; Palmisiano, Neil; Alpdogan, Onder
Abstract : Plasmablastic lymphoma (PBL) is a rare subtype of diffuse large B-cell lymphoma, highly associated with HIV and Epstein-Barr virus (EBV) infections. It commonly presents in extranodal sites, often an oral mass, but reports of primary central nervous system PBL (PCNSPBL) are exceedingly rare. Here, we report on a 33-year-old man with newly diagnosed HIV infection who presented with acute-onset unilateral visual disturbance and was found to have biopsy-proven PCNSPBL. The neoplastic cells displayed a plasmacytoid appearance, with the expression of CD38 and CD138, and were positive for EBV by in situ hybridisation for EBV-encoded RNA. Systemic workup revealed the presence of Kaposi sarcoma, but no evidence of lymphoma. He is currently being treated with high-dose methotrexate, as well as antiretroviral therapy for his HIV infection, and has achieved a complete response.